MODEL MATEMATIKA KESEIMBANGAN PASAR - Dede Ruslan (Universitas Negeri Medan, 2012)
The market is the place where the buyer and the seller are met in order to do various transactions that is based on the numbers of supply and demand. The supply and demand of any goods is affected by the supply and demand of other goods. The equilibrium the market can be overcome if the equilibrium of the price can be achieved. The model of the multi market that has been developed by Samuelson can be changed to homogeny differential equation with the use of stabilizing matrix that can verify that the price can move towards the stabilization of the market equilibrium